Gambaran Radiologi Karsinoma Paru Sentral: Sebuah Laporan Kasus - Inda Kania Meilani; Fransiskus Aryo Pratomo (Universitas Prima Indonesia, 2023)
Lung carcinoma is a malignancy that originates in the respiratory tract and lung parenchyma. It is a type of lung malignancy that often leads to death, characterized by a high mortality rate globally. Based on radiological images, lung carcinoma is classified into central and peripheral types. Understanding the radiological characteristics of lung carcinoma will contribute to achieving swift and appropriate therapy. In this case study, a 46-year-old male patient with smoking history, complaints of breathlessness and a persistent cough is presented. The CT scan findings indicated that the patient had a centrally positioned lung carcinoma, in accordance with the attributes of the central type of lung carcinoma, the scan shows heterogeneous lesions larger than 3 cm situated in the hilum area. The boundaries are somewhat indistinct, displaying irregular edges, spicules, angiogram sign, narrowing and closure of the left main bronchus, the presence of surrounding atelectatic components, and is enhanced by contrast. These findings were corroborated by anatomical pathology examination. This case underscores the pivotal role of radiological modalities in both elucidating and establishing the diagnosis of lung carcinoma.